Profile of physical education teacher personality competency - Jeki Haryanto; Salvetri Salvetri (Global Econedu, 2022)
The physical education teacher's personality competency is still classified as low and needs to be improved so that student comfort during learning becomes better. The learning process that occurs in the classroom and outside the classroom should take place in a fun way, to realize this, it is necessary to have a teacher who has a good personality. This study aims to determine the level of competence of the sports teacher's personality from the point of view of the principal's assessment. This needs to be known to add insight into the competence of the teacher's personality from various existing points of view so that the understanding of the competence of the teacher's personality can be more in-depth. Survey research was conducted to see the principal's assessment of the sports teacher's personality competence. The population in this study were all public elementary school sports teachers in Kerinci Regency, amounting to 228 people. The sampling technique in this study used a simple random sampling technique so that 50 people were selected as samples. Data on the personality competence of sports teachers in this study were collected using a questionnaire. The results of this study indicate that the level of competence of the sports teacher's personality based on the principal's assessment is in the sufficient category. So sports teachers, school principals, and the government need to make programs so that the personality competencies of sports teachers can increase.